Behavioral Determination of the Incidence of Hypertension in the Koya Village Community: Implications for Community-Based Health Interventions - Angellica Francine Pratasik; Gio Enyelysa Gultom; Eunike Febryca Keliat; Injilita Rutemia Donsu; Livia Anatasya Djuweni; Sulfan Arfandi Siriuwa; Bukroanah Amir Makkau (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Goal. Hypertension remains one of the leading contributors to non-communicable disease burden globally and continues to rise in many low- and middle-income communities. This study aims to describe the prevalence of hypertension and identify behavioral risk factors associated with hypertension among residents of Koya Village, Minahasa Regency. Materials and methods. A cross-sectional household survey was conducted involving 30 adult respondents. Primary data were collected through structured interviews and direct household observations. Descriptive analysis was used to examine sociodemographic characteristics, smoking behavior, alcohol consumption, physical activity patterns, and hypertension status. Visual data representation supported the interpretation of behavioral–hypertension patterns within the community context. The results showed that the prevalence of hypertension reached 46.7%, a figure substantially higher than the national average. Smoking behavior was reported by 53.3% of respondents, while 36.7% consumed alcoholic beverages, including traditional high-ethanol drinks. Both behaviors were associated with noticeably higher proportions of hypertension. Physical activity levels were generally low, and routine health monitoring was inconsistent among many respondents. These patterns suggest that behavioral and social determinants strongly influence the risk of hypertension at the community level. The findings confirm that hypertension in Koya Village is shaped by a combination of high-risk behaviors, limited routine health checks, and contextual social norms that reinforce smoking and alcohol consumption. The study underscores the need for community-based promotive and preventive interventions targeting smoking reduction, alcohol control, increased physical activity, and strengthened early detection through primary healthcare services. This research contributes empirical evidence at the micro-community level and provides a contextual foundation for designing more adaptive public health programs.